1999
DOI: 10.3109/08860229909066980
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Study: Oxidative Stress in Chronic Renal Failure

Abstract: This study focuses on the oxidative stress in patients with severe chronic renal failure who are not undergoing dialysis treatment. The erythocyte levels, creatinine clearing and plasma- and cell activities of the following enzymes were determined: glutathione peroxidase (Gpx), superoxide dismutase (SOD), catalase (CAT), glutathione reductase (GR), and glutathione transferase (GT). The concentrations of non-enzyme molecules such as total glutathione in both oxidized and reduced forms, and malonyldialdehyde (MD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
16
0

Year Published

2001
2001
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(20 citation statements)
references
References 12 publications
4
16
0
Order By: Relevance
“…In our study the highest activity of CAT was obtained in conservatively treated CKD3-5 patients. The same results were obtained by Martin-Mateo et al [25]; in their research, CAT activity was significantly higher in non-dialysed patients with CKD compared to healthy controls. Patients on PD had a similar activity of CAT compared to conservatively treated patients and HD patients before the dialysis session.…”
Section: Discussionsupporting
confidence: 78%
“…In our study the highest activity of CAT was obtained in conservatively treated CKD3-5 patients. The same results were obtained by Martin-Mateo et al [25]; in their research, CAT activity was significantly higher in non-dialysed patients with CKD compared to healthy controls. Patients on PD had a similar activity of CAT compared to conservatively treated patients and HD patients before the dialysis session.…”
Section: Discussionsupporting
confidence: 78%
“…Studies on red blood cell GSH-Px activity in CKD patients produced inconsistent results. Some authors found significantly lower (Zachara et al, 2001a;2004a;Bulucu et al, 2000;Martin-Mateo et al, 1999), some -significantly higher (Ceballos-Picot et al, 1996;Mimic-Oka et al, 1992) and still others did not observe any differences (Zachara et al, 2004b;Temple et al, 2000). It can be concluded that bone marrow in CKD patients is not damaged and the synthesis of this enzyme does not deviate from the norm.…”
Section: Glutathione Peroxidase Activities In the Blood Of Patients Imentioning
confidence: 80%
“…[28,29] Other factors have been studied to clarify the causes of this hypertension, including high levels of vasoconstrictors, oxidative stress or nitric oxide (NO) reduction. [6,[26][27][28][29][30][31] In CRF patients, oxidative stress and inflammation could play a crucial role in the pathogenesis of the atherosclerosis, malnutrition, and anaemia. In our model of moderate renal failure, the redox state seems to be unaltered (MDA/TAS ratio was unchanged), which might be due to a proper compensation of ROS formation by antioxidants.…”
Section: Tablementioning
confidence: 99%